Optimizing Environmental Sanitation as an Effort to Control Dengue Fever (DBD) Vectors - Saskia Diah Nisa (Journal Health of Indonesian, 2025)
Dengue Hemorrhagic Fever (DHF) is an endemic disease caused by dengue virus infection transmitted through the main vector, the Aedes aegypti mosquito. Transmission of this disease is influenced by environmental factors, human behavior, and inadequate sanitation conditions. This article aims to discuss effective environmental sanitation management in suppressing the Aedes aegypti vector population and preventing the spread of DHF. Several aspects analyzed include the provision of clean water, the habit of hanging clothes, management of water reservoirs (TPA), the condition of trash bins, and the presence of pots or other containers that have the potential to become mosquito breeding grounds. Good environmental management, such as the application of the 3M method (Draining, Covering, and Recycling), the use of larvicide, and routine cleaning of places that have the potential to become mosquito nests, has been proven to be able to significantly reduce vector density. In addition, planning vector eradication through abatization and fogging methods in densely populated areas is also a strategic step in reducing DHF cases. By increasing public awareness of the importance of environmental sanitation, it is hoped that dengue virus transmission can be minimized, so that extraordinary events (KLB) of DHF can be prevented.